IoT monitoring of a master-slave robot system using MIT App Inventor / Siti Noramira Zulkarnain ... [et al.] - Zulkarnain, Siti Noramira; Ahmad Shauri, Ruhizan Liza; Saidin, Mohamad Haidil; Afiqie Zamanhuri, Ahmad Zaidiel (UiTM Press, 2024)
A previously developed 4-DOF master-slave robot system showed that the master device was able to control the motion of the slave robot but due to the wired connection between the systems, the user must be in the same room to monitor the robot’s movement. In order to monitor the robot operation wirelessly from a distance or outside of the laboratory room, an IoT-based platform is desirable. With the IoT method selected, the interface between the application, hardware and software is essentially important. Each part requires specific programming codes to ensure transmission of data runs smoothly between the chosen interface platforms. MIT App Inventor was selected as the IoT application that uses Firebase Cloud for storing data acquired from the master and slave controllers. Bluetooth modules are used as the interface between the master and slave controllers, while NodeMCU ESP32 enables the Wi-Fi connectivity between all three i.e. the controllers, the cloud storage and the MIT App Inventor. As a result, selected robot data were observed to be viewable from the user’s mobile devices using the MIT AI2 companion application. The verification test with the execution of the robot showed that the IoT platform has successfully displayed numerical and graphical data of the desired robot’s joint angle and motor increments from the master and the slave controllers, respectively, based on several user’s arm gestures measured by force sensors.